Morphology based anisotropic finite element models of the proximal femur validated with experimental data. Issue 11 (November 2016) - Enns-Bray, W.S.; Ariza, O.; Gilchrist, S.; Widmer Soyka, R.P.; Vogt, P.J.; Palsson, H.; Boyd, S.K.; Guy, P.; Cripton, P.A.; Ferguson, S.J.; Helgason, B.
Highlights: No change in stiffness correlation between sideways fall FE models with isotropic and anisotropic material properties. Up to 14% difference in principal compressive strain of internal elements in femoral neck, head, and greater trochanter. Changes in nodal strain due to anisotropy were limited to internal nodes, with minimal effect observed in surface strains. Degree of anisotropy of trabecular bone could be underestimated by the conventional MIL measurement technique. Abstract: Finite element analysis (FEA) of bones scanned with Quantitative Computed Tomography (QCT) can improve early detection of osteoporosis. The accuracy of these models partially depends on the assigned material properties, but anisotropy of the trabecular bone cannot be fully captured due to insufficient resolution of QCT. The inclusion of anisotropy measured from high resolution peripheral QCT (HR-pQCT) could potentially improve QCT-based FEA of the femur, although no improvements have yet been demonstrated in previous experimental studies. This study analyzed the effects of adding anisotropy to clinical resolution femur models by constructing six sets of FE models (two isotropic and four anisotropic) for each specimen from a set of sixteen femurs that were experimentally tested in sideways fall loading with a strain gauge on the superior femoral neck. Two different modulus–density relationships were tested, both with and without anisotropy derived from mean intercept length analysis of HR-pQCT scans. Comparing iso- and anisotropic models to the experimental data resulted in nearly identical correlation and highly similar linear regressions for both whole bone stiffness and strain gauge measurements. Anisotropic models contained consistently greater principal compressive strains, approximately 14% in magnitude, in certain internal elements located in the femoral neck, greater trochanter, and femoral head. In summary, anisotropy had minimal impact on macroscopic measurements, but did alter internal strain behavior. This suggests that organ level QCT-based FE models measuring femoral stiffness have little to gain from the addition of anisotropy, but studies considering failure of internal structures should consider including anisotropy to their models.